Linkage of azurophil granule secretion in neutrophils to chloride ion transport and endosomal transcytosis. - Fittschen, C (1994)
Neutrophils contain at least two types of secretory granules. The present work links the secretion of the (lysosomal type) azurophil granules, but not that of specific granules, to endosomal transport mechanisms. (a) Selective stimulation of azurophil granule secretion by the Na-ionophore Monensin, or nonselective stimulation by FMLP after cytochalasin B pretreatment elicited marked pinocytic activity in parallel with azurophil granule release, whereas FMLP alone, selective for specific granules, elicited little fluid pinocytosis. (b) Pinosomes thus formed fused with azurophil granules, suggesting that exocytosis of azurophil granules might occur via endosomal organelles. This hypothesis was tested by determining the effect on the endosomal pathway(s) of two treatments that selectively prevent the release of azurophil granule contents without interfering with specific granule secretion, namely replacement of Cl- with gluconate- or the addition of zinc. Replacement of Cl- was found to impair the pinocytosis process itself, whereas ZnSO4 appeared to prevent the fusion between endosomes and azurophil granules. These data support the concept that the (lysosomal type) azurophil granules, but not the specific granules, are secreted through the endosomal pathway.